Retention and processing methods of nasal prosthesis - Goiato, Marcelo Coelho [UNESP]; Mancuso, Daniela Nardi; Zuccolotti, Bruna Carolina Rossati; Murakawa, Ana Cristina; Lima, Daniela Coelho de; Santos, Daniela Micheline dos [UNESP]; Andreotti, Agda Marobo (My University, 2012)
Patients with congenital malformations, traumatic or pathological mutilation and maxillofacial developmental disorders can be restored aesthetically and emotionally by the production and use of facial prostheses. The aim of this study was to review the literature about the retention and processing methods of facial prostheses, and discuss their characteristics. A literature review on Medline (PubMed) database was performed by using the keywords maxillofacial prosthesis, silicone, resin, pigment, cosmetic, prosthetic nose, based on articles published from 1956 to 2010. Several methods of retention, from adhesives to the placement of implants, and different processing methods such as laser, CAD/CAM and rapid prototyping technologies have been reported. There are advantages and disadvantages of each procedure, and none can be classified as better compared to others.
Keywords: Cosmetic; Nasal prostheses; Pigment; Resin; Silicone; adhesive agent; cosmetic; pigment; resin; silicone; bibliographic database; face malformation; human; implant; laser; maxillofacial prosthesis; medical literature; Medline; nose prosthesis; Adhesives; Computer-Aided Design; Craniofacial Abnormalities; Humans; Maxillofacial Prosthesis; Nasal Surgical Procedures; Nose; Prosthesis Design; Prosthesis Failure; Prosthesis Implantation; Reconstructive Surgical Procedures; Resins, Synthetic